COVID-19 Vaccination in Pediatric Population: A Necessity or Obstruction to the Protection of the Right to Health? Biojuridical Perspective - Bilotta, Clio; Perrone, Giulio; Zerbo, Stefania; Argo, Antonina (Frontiers in Public Health, 2022)
One of the most debated topics recently concerns the mass vaccination of children against COVID-19. It was then discussed on the comparison of the risk / benefit ratio of COVID-19 vaccination and infection in children. The question is: does the vaccine represent a necessary tool or an obstacle to protect the right to health? The Supreme Court of Nova Scotia, in Canada, recommends the vaccinations in support of public health. The vaccination could be considered a social act necessary for the protection of the right to health, by invoking Article 25 of the Draft Articles on State Responsibility. The 1989 New York Convention on the Rights of the Child and today the European Regulation no. 219/1111 expressly state that the opinion of the minor who has completed the twelfth year of life has its weight, although in relation to age and his degree of discernment. It is not excluded that the onset of adverse events following the administration of the COVID-19 vaccine may lead to compensation in the near future. Recent studies have identified a new COVID-19-related pediatric pathology, known as multisystem inflammatory syndrome (MIS-C); others demonstrate myocarditis with positive outcome, caused by COVID-19 vaccine. In June 2021 in the USA, the CDC Advisory Committee on Immunization Practices declared that the benefits of vaccination against COVID-19 for the pediatric population outweighed the risks. It will be appropriate to monitor the real risk/benefit ratio of vaccination in the pediatric population. In the meantime, the bioethical debate on this question remains open.